Political Economy of Media in Spatial Representation of National Geographic Indonesia’s Youtube Content - Londaleta, Eltie Elisabeth (Journal Commedies, 2025)
Abstract National Geographic Indonesia is a monthly magazine covering nature, the environment, geography, science, and other topics. Advances in communication technology have led this media outlet to sell its products not only in physical magazines but also through digitalization, changing its sales system to its website. In addition to selling its magazines digitally, National Geographic Indonesia also operates several social media platforms, including Facebook, Twitter, Instagram, and YouTube. Simply put, the purpose of these websites and social media platforms is to ensure its products reach all audiences across Indonesia and the world. This brief study aims to determine how National Geographic Indonesia spatializes political economy through its broadcasts on National Geographic Indonesia’s YouTube videos. The method used is content analysis of text and YouTube videos. The results show that the concept of political economy spatialization in both videos was discovered by analyzing the video content based on the broadcasts and text or sentences within the videos. The spatialization context in the video is distinguished by several aspects, including spatial representation, the commodification of space and resources, political economy, space as an ideological construct, and spatialization and distribution chains. Keywords: Political Economy, Spatialization, National Geographic Indonesia.